2002
DOI: 10.1128/jvi.76.14.6909-6918.2002
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Binds to Murine Leukemia Virus and Inhibits Env-Independent Attachment and Infection

Abstract: Certain glycosaminoglycans (GAGs), including heparin, inhibit infection by murine leukemia virus (MLV).We now show that this is due to inhibition of virus attachment independent of the interaction between viral envelope proteins (Env) and their cellular receptors. Heparin blocked the binding of both Env-deficient and amphotropic MLV (MLV-A) particles to NIH 3T3 fibroblasts, CHO cells which lack the amphotropic retroviral receptor Pit-2, and CHO cells transfected with Pit-2 (CHO-Pit-2). Heparin also inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Previously it was demonstrated that infection by HIV-1 is promoted by GAGs on target cells but only for HIV-1 isolates carrying a viral Env protein with a highly positively charged V3-loop (38). In our system, we observed virus surfacing even for cells generating Gag-CFP in the absence of MLV Env (data not shown), consistent with the notion that MLV's association with GAGs or alternative receptors on infected XC cells is not necessarily Env dependent (11,24,25,35). Polybrene treatment switches surfacing to surfing on infected cells.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Previously it was demonstrated that infection by HIV-1 is promoted by GAGs on target cells but only for HIV-1 isolates carrying a viral Env protein with a highly positively charged V3-loop (38). In our system, we observed virus surfacing even for cells generating Gag-CFP in the absence of MLV Env (data not shown), consistent with the notion that MLV's association with GAGs or alternative receptors on infected XC cells is not necessarily Env dependent (11,24,25,35). Polybrene treatment switches surfacing to surfing on infected cells.…”
supporting
confidence: 75%
“…Retroviruses including MLV and HIV are able to bind to cells through interactions with cell surface glycosaminoglycans (GAGs) (34,35), notably heparan sulfate (7,11), even in the absence of specific viral receptor molecules. To test if the retention and motility of assembled viruses at the infected-cell surface reflected an association with GAGs, we initiated live-cell imaging prior to the addition of heparinase II, which cleaves heparan FIG.…”
Section: Resultsmentioning
confidence: 99%
“…For retroviruses, this initial step in the virus life cycle was for a long time believed to be mediated solely by the viral Env protein. However, the presence of cellular components on the MMLV surface responsible for promoting viruscell attachment has been proposed (17,53,69). To date, these components remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Heparan sulfates, which are widely expressed on the surface of cells, have been shown to be used by a number of viruses including the retroviruses HIV-1 and murine leukemia virus (24,25). More recent studies have revealed that heparan sulfate proteoglycans (HSPG) can also specifically bind soluble HTLV SU and enhance entry of HTLV-I pseudotypes (26,27).…”
Section: Induction Of Human T Cell Leukemia Virus Type I Receptors Onmentioning
confidence: 99%